Pendapatan dan Gaya Hidup Sebagai Determinan Keputusan Investasi Emas pada ASN Kabupaten Nagan Raya - Martini, Martini; Muzakir, Muzakir; Makmun, Abu Hassan (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
Gold investment decisions among State Civil Servants (ASN) remain an issue; although they possess relatively stable incomes, not all of them utilize their earnings to invest in gold. Furthermore, previous research regarding the influence of income and lifestyle on gold investment decisions has yielded inconsistent findings. This study aims to analyze the impact of income and lifestyle on gold investment decisions among ASN in Nagan Raya Regency. A quantitative approach was employed with a sample of 98 respondents selected via purposive sampling, and data analysis was conducted using multiple linear regression with the aid of IBM SPSS Statistics. The results indicate that, individually, income has a positive and significant effect on gold investment decisions, whereas lifestyle does not have a significant effect. However, when considered simultaneously, both income and lifestyle significantly influence gold investment decisions. The R² of 0.338 indicates that 33.8% of the variation in gold investment decisions can be explained by these two variables, while the remainder is influenced by factors outside the scope of this study. The study implies that enhancing the financial capacity and financial planning of ASN is crucial for encouraging gold investment, whereas lifestyle is not a primary determinant of investment decisions when analyzed in isolation.